Analysing employee behavior to improve organizational performance at pt. Dki - Kurniati, Diah; Welly, John (The Indonesian Journal of Business Administration, 2018)
Abstract. The impact of global competition in legal service providers and global economic preasure lead to many lawfirm in Asia-Pasific face difficult in balancing between compensation and talents. That also happened in PT. DKI lawfirm which faced high turnover rate and low employee performance in internal management. Therefore, PT. DKI law firm is looking for a way to improve organizational performance and employee behavior and lower turnover rate to compete with other corporate law firms using MAE model (Behavior = Motivation, Ability and Environment) and action research framework. The purpose of this research is to find out what drivers in MAE Model caused high turnover and decrease of employee performance in company. This model analyzes nine drivers that are the main components in the formation of organized behaviors: Recruitment, Selection, Training, Performance Management, Compensation, Culture, Organizational Development, Organizational Design and Human Resource Planning. All data collection is done through quantitative and qualitative methods. Primary data were collected from the questionnaire and then the results of the questionnaires were made into the material by the researcher to analyze the current condition of the company and make a solution to the problem solving. In making problem solving proposals, researcher involves representatives of employees to diagnose and plan corrective measures. The results of the joint diagnosis and joint planning are then re-presented to management for review or improvement and given decisions on the implementation of improvement plan.Keywords: Employee Behavior, Organizational Performance, MAE Model, Action Research Model, Legal Service Provider